An Evaluation of the Longitudinal, Bidirectional Associations Between Gait Speed and Cognition in Older Women and Men. (10th April 2016) - Best, John R.; Liu-Ambrose, Teresa; Boudreau, Robert M.; Ayonayon, Hilsa N.; Satterfield, Suzanne; Simonsick, Eleanor M.; Studenski, Stephanie; Yaffe, Kristine; Newman, Anne B.; Rosano, Caterina; ,
Abstract: Background: Few cohort studies have examined longitudinal associations between age-related changes in cognition and physical performance. Further, whether these associations differ for men versus women or can be attributed to differences in physical activity (PA) is unknown. Methods: Participants were 2, 876 initially well-functioning community-dwelling older adults (aged 70–79 years at baseline; 52% female; 39% black) studied over a 9-year period. Usual gait speed, self-reported PA, and two cognitive measures—Digit Symbol Substitution Test (DSST) and Mini-Modified Mental State examination (3MS)—were assessed years 0 (ie, baseline), 4, and 9. Results: Early decline between years 0 and 4 in gait speed predicted later decline between years 4 and 9 in performance on the 3MS (β = 0.10, p = .004) and on the DSST (β = 0.16, p < .001). In contrast, the associations between early decline in cognition and later decline in gait speed were weaker and were non-significant after correcting for multiple comparisons (β = 0.08, p = .019 for 3MS and β = .06, p = .051 for DSST). All associations were similar for women and men and were unaltered when accounting for PA levels. Conclusions: The results indicate declining gait speed as a precursor to declining cognitive functioning, and suggest a weaker reciprocal process among older women and men.